2022
DOI: 10.3390/jcm11123379
|View full text |Cite
|
Sign up to set email alerts
|

How Does SARS-CoV-2 Affect Our Eyes—What Have We Learnt So Far about the Ophthalmic Manifestations of COVID-19?

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has become a worldwide threat resulting in a pandemic in 2020. SARS-CoV-2 infection manifests itself as coronavirus disease 2019 (COVID-19) that is evidenced in a vast number of either specific or nonspecific symptoms. Except for typical (but nonspecific) symptoms such as fever, dry cough, or muscle weakness, the infected patients might also present atypical symptoms including neurological, dermatological, or ophthalmic manifestations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 121 publications
0
6
0
1
Order By: Relevance
“…While COVID-19 primarily manifests as a respiratory illness, reports of ocular symptoms and complications have emerged [ 2 ]. The exact pathogenesis of how COVID-19 may contribute to orbital cellulitis remains unclear but warrants further investigation [ 2 , 3 ]. It is conceivable that COVID-19-related immunomodulation and inflammation may create a favorable environment for secondary infections such as those seen in our case [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…While COVID-19 primarily manifests as a respiratory illness, reports of ocular symptoms and complications have emerged [ 2 ]. The exact pathogenesis of how COVID-19 may contribute to orbital cellulitis remains unclear but warrants further investigation [ 2 , 3 ]. It is conceivable that COVID-19-related immunomodulation and inflammation may create a favorable environment for secondary infections such as those seen in our case [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The book Ophthalmic Manifestations Of Coronavirus (COVID-19) claims that 2-32% of patients with COVID-19 present ocular symptoms (9). SARS-CoV-2 infection can affect anatomical eye sites such as the anterior and posterior segments, appendages, and nerves, and it can lead to such common symptoms as conjunctivitis and to rare ones such as retinal arteriovenous obstruction, optic neuritis, uveitis, and orbital lesions (10)(11)(12). A meta-analysis of 43 studies with 10,572 participants showed that patients with COVID-19 had a high prevalence of conjunctivitis, ptosis, ophthalmoplegia, cotton wool spots, retinal hemorrhages, and retinal vein tortuosity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Conjunctivitis may be associated with the involvement of the surrounding tissue such as the eyelid margins and cornea in blepharoconjunctivitis and viral keratoconjunctivitis, respectively [4] Figure 1: Eye Flu (Pink Eye) II. CAUSES [5,6,7] Eye flu is an infectious disease; thus, it is important to know its causes. The major causes of eye flu disease are:…”
Section: Introductionmentioning
confidence: 99%